Enjoying Bakpia by exploring the Spirit of Tut Wuri Handayani - Pramudito, Aditya; Huda, Dimas Rizky; Fitriana, Regita Nova; Permatasari, Sekar Putri; Sebri, Muhammad; Maulida, Alfiatul (PT Inovasi Pratama Internasional, 2024)
The main objective of this program is to provide training and guidance in the social and environmental fields that focus primarily on the development of MSMEs. Community service activities carried out by students and lecturers of the Management Study Program, Sarjanawiyata Tamansiswa University on October 11, 2024 at Bakpia Zahrae 215 have the theme